Analysis of the Impact of Harmful Algal Bloom (HAB) on Productivity in The Java Sea Waters - Muhammad Reza Falevi; Tegar Al-Ghifari Widiantara; Livela Rahmalia Azzahra; Aisyah Nur’aini; Muhammad Rizqy Ramadhani Hidayatulloh; Fajar Adiyanto (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2026)
Harmful Algal Bloom (HAB) is an ecological phenomenon that has been increasingly occurring in the Java Sea and has the potential to significantly affect marine productivity. However, studies that integrate multiple HAB triggering factors and their impacts on marine productivity in the Java Sea remain limited and largely fragmented. This study aims to analyze the influence of HAB on marine productivity in the Java Sea through a literature review approach. A total of 20 scientific articles published between 2015 and 2025 were analyzed, consisting of 6 primary articles and 14 supporting articles, with the main focus on coastal areas of the Java Sea. The review results indicate that the primary drivers of HAB occurrence in the Java Sea include increased nutrient concentrations (nitrate and phosphate), changes in oceanographic conditions (temperature, salinity, and current dynamics), and anthropogenic pressures in coastal regions. Dominant HAB-forming phytoplankton species were reported from the Dinoflagellata and Bacillariophyceae groups, which under certain conditions may quantitatively enhance marine productivity; however, this increase is considered pseudo-productivity due to subsequent declines in dissolved oxygen, disruption of food web structures, and elevated risks of toxicity to aquatic organisms. The novelty of this study lies in the integrated synthesis of the relationship between HAB drivers and their implications for marine productivity within the Java Sea. These findings emphasize that increased water fertility does not necessarily correspond to enhanced marine productivity, highlighting the importance of nutrient and coastal activity management to ensure the sustainability of the Java Sea ecosystem.